BENTUK PENYAJIAN TARI JEPIN LANGKAH PENIBONG KABUPATEN MEMPAWAH KALIMANTAN BARAT - Ardiansyah, Deki Prasetya; Syahrani, Agus; Fertisari, Imma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is 1) to describe the form of presentation of dance jepin Penibong steps, 2) describe the implementation of dance moves in Jepin Step Penibong on art and culture lessons. The method used is descriptive method with qualitative form and using ethnokoreologi approach, with data source Usman Muhammad Ali who knows about the form of dance performances jepin Penibong step in Mempawah district. The data obtained is the result of interviews, observation and documentation. Jepin Step Dance performed by Daeng bacok Alm from Riau Province. The costumes used for dance Jepin Step Penbong is a baju kurung for women and telok belanga for men while the makeup is used beautiful makeup. The music that accompanied the dance jepin step this pennong is a melayu music that comes from gambus and beruas and accompanied by poetry. Jepin Dance Step Penperong is danced on an open stage or a closed stage. The results of this study is expected to be implemented in the art culture of SMP class VII second semester. Research it is suggested that the Jepin Dance Step Penibong must be preserved so as not to experience extinction. Culture, arts institutions, and society is expected to preserve dance Jepin Penibong steps, so this dance can be maintained and developed. Keywords: pengajian form, Jepin step Penibong